Empowerment in T. D. Jakes’ Motivational Discourse " Courage “: A Positive Discourse Analysis (Texas Journal of Multidisciplinary Studies, 2023)
Positive Discourse Analysis (PDA) as a new complementary direction of Critical Discourse Analysis (CDA) attempts to investigate how language is positively used by T.D Jakes in his well-known motivational speech "Courage", in which the ideology of empowerment is highly-expressed through motivating, encouraging and reinforcing every frustrated human being listening to his speech. Investigating the discursive strategies, by which empowerment is expressed, is the problem of the present study. Methodologically, there is a need for making a theoretical survey of PDA, developing an appropriate model, then doing a qualitative and quantitative analysis of the motivational speech "Courage". In conclusion, the discursive strategies are syntactic (sentence types/conditionals), rhetorical strategies (repetition/metaphor/personification) and ideological strategies ( emphasizing goods / de-emphasizing negatives )